2015
DOI: 10.1007/s00253-015-6997-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteins, peptides, polysaccharides, and nucleotides with inhibitory activity on human immunodeficiency virus and its enzymes

Abstract: Human immunodeficiency virus (HIV), the causative agent of acquired immune deficiency syndrome, has claimed innumerable lives in the past. Many biomolecules which suppress HIV replication and also other biomolecules that inhibit enzymes essential to HIV replication have been reported. Proteins including a variety of milk proteins, ribosome-inactivating proteins, ribonucleases, antifungal proteins, and trypsin inhibitors; peptides comprising cathelicidins, defensins, synthetic peptides, and others; polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 137 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…45,46 Regarding basis, it was previously found that uracil influences quorum sensing and biofilm formation in Pseudomonas aeruginosa. 47 In addition, nucleosides and/or nucleotides and their analogues showed inhibitory activity towards different viruses (e.g., HIV, HBV) 48,49 , and regulate virulence factors, biofilm formation and quorum sensing in Pseudomonas. 50 Our previous investigations showed about 25 fold higher concentration of quinic acid in an edible mushroom 51 (478 g g -1 fresh) than in C. intybus red chicory (<20 g g -1 fresh).…”
Section: Resultsmentioning
confidence: 99%
“…45,46 Regarding basis, it was previously found that uracil influences quorum sensing and biofilm formation in Pseudomonas aeruginosa. 47 In addition, nucleosides and/or nucleotides and their analogues showed inhibitory activity towards different viruses (e.g., HIV, HBV) 48,49 , and regulate virulence factors, biofilm formation and quorum sensing in Pseudomonas. 50 Our previous investigations showed about 25 fold higher concentration of quinic acid in an edible mushroom 51 (478 g g -1 fresh) than in C. intybus red chicory (<20 g g -1 fresh).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be noted that some bacterial and fungal enzymes targeting the sarcin-ricin loop have also been reported to possess antiviral activity [2,[67][68][69][70][71][72][73].…”
Section: Citotoxicity Of Ripsmentioning
confidence: 99%
“…Strategies are also being searched to tackle the challenge of plant viruses causing significant crop losses. This has led to the discovery of a number of antivirals with different chemical nature or proteins with different enzymatic activities [1,2]. The search for more effective and safer antivirals continues to be a field of intense investigation and plants are one of the most used sources, since they have evolved a variety of protein-based defense mechanisms to tackle viral infections [3].…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral effect. LF, β-LG, and α-LA have shown an antiviral role against human immunodeficiency virus (HIV) by inhibiting the activity of reverse transcriptase, integrase, and protease (Ng et al 2015).…”
Section: Minor Milk Proteinsmentioning
confidence: 99%